Proceedings of the 2nd International Colloquium on Sports Science, Exercise, Engineering and Technology 2015 (ICoSSEET 2015) - Ismail, Shariman Ismadi; Sulaiman, Norasrudin; Adnan, Rahmat; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The proceeding is a collection of research papers presented at the 2nd International Colloquium on Sports Science, Exercise, Engineering and Technology (ICoSSEET2015), a conference dedicated to address the challenges in the areas of sports science, exercise, sports engineering and technology including other areas of sports, thereby presenting a consolidated view to the interested researchers in the aforesaid fields. The goal of this conference was to bring together researchers and practitioners from academia and industry to focus on the scope of the conference and establishing new collaborations in these areas. The topics of interest are in mainly (1) Sports and Exercise Science (2) Sports Engineering and Technology Application (3) Sports Industry and Management.
Enhancement Effects of Tongkat Ali (Eurycoma Longifolia) Supplementation on Performance Functions Following Strength Training in Middle-aged Women -- Effects of Age on Physical Activity Level, Strength and Balance towards Fall Risk Index Among Women Aged 20-73 Years Old -- Gender Differences On The Sources of Anxiety and Level of Sport Performance Among Malaysia Athletes -- The Effect of Enhanced Sensorymotor Feedback on Balance among Football Players -- Development of Portable Biofeedback Devices for Sport Applications.  .
Keywords: Biomedical engineering; Biophysics; Sports medicine; Nutrition .; Biomedical Engineering and Bioengineering; Biophysics; Sports Medicine; Nutrition